4-hydroxybenzophenone exposure inhibits mouse hippocampal neural stem cell proliferation in vitro by upregulating Cxcl1. (August 2022) - Lin, Yahang; He, Min; Zeng, Xiaoyun; Sheng, Xia; Wang, Siyi; Cui, Fengzhen
Abstract: Benzophenones are widely used in industry and commonly added in many personal care products. However, the neurotoxicity, in particular neurodevelopmental toxicity, of benzophenone family chemicals and metabolites has not been fully elucidated. Our recent mechanistic study in mice showed that early life exposure to a major benzophenone metabolite, 4-hydroxybenzophenone (4HBP), disrupted endoplasmic reticulum (ER) proteostasis and evoked inflammatory response in hippocampal neural stem cells (NSCs), leading to cognitive dysfunction. Despite so, detailed inflammatory cytokine(s) that possibly mediate this toxicity remains to be defined and validated. In this study, we confirmed that 4HBP treatment inhibited the viability and sphere growth of mouse NSCs in vitro . Importantly, re-interrogation of the transcriptomic data of NSCs treated with 4HBP identified the top upregulated genes, wherein the chemokine Cxcl1 ranked first. Immunofluorescent staining and qRT-PCR validated the robust induction of Cxcl1 on the protein and mRNA levels upon 4HBP treatment. Furthermore, siRNA-mediated knockdown of Cxcl1 transiently blocked its expression and led to enhanced NSCs viability in the presence of 4HBP. Together, these in vitro results indicated that the adverse effect of benzophenones on NSCs is mediated, at least in part, by induction of the chemokine Cxcl1. Highlights: Exposure to 4-hydroxybenzophenone (4HBP) inhibited the viability and sphere growth of primary mouse neural stem cells (NSCs) in vitro. Transcriptome data of NSCs treated with 4HBP showed that Cxcl1 was the first up-regulated gene. Knockdown of Cxcl1 transiently blocked its expression and led to enhanced NSCs viability in the presence of 4HBP.